(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the features of the traditional economy of the Pamir Kyrgyz in the late 19th – early 20th centuries. The Pamir Kyrgyz, who lived in the hard-to-reach highland regions of the Pamirs, led a semi-nomadic lifestyle adapted to harsh natural conditions. The basis of their economy was cattle breeding, mainly yaks, sheep and goats. Yaks were especially important for the Pamir Kyrgyz, as they were well adapted to life in the highlands and provided people with milk, meat, wool and were used as draft animals. Agriculture also played an important role in the economy of the Pamir Kyrgyz. They grew barley, wheat, potatoes and other crops that could survive in the conditions of a short growing season and lack of fertile land. Agriculture in the Pamirs was possible due to the creation of artificial irrigation systems that made it possible to deliver water from the mountains to the fields. Crafts were developed among the Pamir Kyrgyz, especially the manufacture of felt products such as yurts, carpets and clothing. Felt was not only a material for housing and clothing, but also an important item of exchange. Trade played an important role in the economy of the Pamir Kyrgyz. They exchanged cattle, wool, felt and other goods for grain, fabrics, metal products and other necessary things with neighboring peoples. Trade was carried out both within the region and with distant areas such as Kashmir, China and Turkestan. The traditional economy of the Pamir Kyrgyz in the late 19th – early 20th centuries was based on a combination of cattle breeding, agriculture and crafts, which allowed them to survive and adapt to the difficult conditions of the highlands. It provided them with basic food products, clothing and other necessary things. At the beginning of the 20th century, due to the establishment of Soviet power in the Pamirs and changes in the socio-economic structure of society, the traditional economy of the Pamir Kyrgyz began to undergo changes, but many of its elements remained until recently.